Emergent Positioning in Insider Ethnographic Field: Deconstructing the Ideological Frame of Insider or Outsider or Both - Rai, Indra Mani (Dhaulagiri Journal of Sociology and Anthropology, 2020)
The central concern of this paper is to discuss the positioning of the researcher while researching one’s own community ethnographically. It argues that insider and outsider positioning of a researcher in insider ethnographic research appears in a contextual, iterative, and emergent manner. The strategies provide space for critical self-reflexive practices in the field, thereby enhancing the quality standard. In addition, it argues that the positioning of the researcher appears while maintaining the ethical issue of confidentiality. Thus, the paper claims that it is not necessary to set the ideological frame for structuring the researchers whilst engaging in the field with particular positioning. It highlights that the defined roles of a researcher guide him/her in a way denying to engage in the field adapting the contextual phenomena, thereby creating difficulties for generating quality data.